Edaravone alleviates cell apoptosis and mitochondrial injury in ischemia–reperfusion-induced kidney injury via the JAK/STAT pathway - Zhao, Xiaoying; Zhang, Erfei; Ren, Xiaofen; Bai, Xiaoli; Wang, Dongming; Bai, Ling; Luo, Danlei; Guo, Zheng; Wang, Qiang; Yang, Jianxin (Biological research, 2020)
Kidney ischemia-reperfusion injury is a common pathophysiological phenomenon in the clinic. A large number of studies have found that the tyrosine protein kinase/signal transducer and activator of transcription (JAK/STAT) pathway is involved in the development of a variety of kidney diseases and renal protection associated with multiple drugs. Edaravone (EDA) is an effective free radical scavenger that has been used clinically for the treatment of postischemic neuronal injury. This study aimed to identify whether EDA improved kidney function in rats with ischemia-reperfusion injury by regulating the JAK/STAT pathway and clarify the underlying mechanism. Histomorphological analysis was used to assess pathological kidney injury, and mitochondrial damage was observed by transmission electron microscopy. Terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) staining was performed to detect tubular epithelial cell apoptosis. The expression of JAK2, P-JAK2, STAT3, P-STAT3, STAT1, P-STAT1, BAX and Bcl-2 was assessed by western blotting. Mitochondrial function in the kidney was assessed by mitochondrial membrane potential ([DELA]Î¨m) measurement. The results showed that EDA inhibited the expression of p-JAK2, p-STAT3 and p-STAT1, accompanied by downregulation of the expression of Bax and caspase-3, and significantly ameliorated kidney damage caused by ischemia-reperfusion injury (IRI). Furthermore, the JC-1 dye assay showed that edaravone attenuated ischemia-reperfusion-induced loss of kidney [DELA]Î¨m. Our findings indicate that EDA protects against kidney damage caused by ischemia-reperfusion through JAK/STAT signaling, inhibiting apoptosis and improving mitochondrial injury.